Initial Extremity War Wound Debridement: A Multidisciplinary Consensus. Issue 2 (1st June 2011) - Guthrie, HC; Clasper, JC; Kay, AR; Parker, PJ
Abstract : A joint meeting of the Limb Trauma and Wounds Working Groups resulted in the establishment of 29 consensus recommendations for the conduct of initial extremity war wound debridement. Pre-operative, operative and post-operative phases of debridement were considered along with wound irrigation and dressings. Wounds where a different surgical approach is required, such as superficial soft tissue wounds at one end of the spectrum and complex wounds sustained in close proximity to explosions at the other, were also discussed. The recommendations represent the consensus opinion of orthopaedic, vascular and plastic surgeons, as well as nursing officers, from across the Defence Medical Services and are intended to provide useful guidance to the deploying surgeon, regardless of their own personal experience.